OPEN DATA CULTURE IN SOCIAL SCIENCE RESEARCH - Basak, Rituparna (International Journal of Research -GRANTHAALAYAH, 2023)
Open data are records that are available for anybody to access, reuse, and distribute without restriction, with the exception of sharing and attribution. Many national governments have created websites to make some of the data they gather accessible to public, joining private companies in doing so. The creation of such massive archives is expected to promote and speed scientific progress by allowing multiple uses of datasets and minimizing duplication of effort Hand et al. (2001). When a repository is fully made up of datasets supplied by researchers and made accessible for use by other researchers, future uses of such datasets are referred to as reuse. When it comes to reusing research data in the social sciences, it has been discovered that quantitative data reuse is more widespread than qualitative data reuse since the number of free quantitative datasets is bigger Curty et al. (2017) and quantitative data metadata is easier to develop. Nonetheless, there is various research on the reuse of qualitative data in social sciences Late & Kekäläinen (2020). Despite several issues that must be addressed, it is obvious that open access data has the potential to transform research processes in a variety of sectors.